Citizen Participation and Public Trust in Local Government: The Republic of Korea case - Kim, Soonhee; Lee, Junesoo; Lee, Jooho (OECD Journal on Budgeting, 2018)
Over the past decades, leaders and citizens in many countries have lamented the lack of transparency in government and declining citizens’trust in government. South Korea is not an exception. In order to restore trust in government, the Korean government has made considerable efforts to adopt and promote various citizen participation programmes at all levels of government in an effort to ensure accountability, improve transparency and trust in government. This article first discusses the importance of citizen participation as a means of improving transparency and trust in government. It then introduces offline and online citizen participation programmes run by central agencies and local governments and highlight how those citizen participation programmes have evolved. As one specific form of citizen participation practice, this article focuses on the practice of Participatory Budgeting (PB) as an effort to enhance transparency and citizens’trust in government by opening its processes and disclosing budgeting information to the public. Most especially, this article reveals the results of a PB survey of local governments in Korea and discusses why and how PB has been adopted, implemented, and designed to improve budget-related governance structure, policy-making processes, and outputs such as efficiency, accountability, transparency, and trust in government. Lastly, this article discusses policy implications for enhancing public trust in government through PB.